Harvesting the heart - Picoult, Jodi, 1966- (New York : Penguin Books, 1995)
The author of Picture Perfect "explores the fragile ground of ambivalent motherhood" (New York Times Book Review). Paige's mother left when she was five. When Paige becomes a mother herself, she is overwhelmed by the demands. Unable to forget her past, Paige struggles with the difficulties of marriage and motherhood.
890
Accelerated Reader AR
Keywords: Women -- United States -- Fiction; Domestic fiction